Determinasi Keberterimaan Toko Pertanian terhadap Pupuk Ribost di Kecamatan Rejoso Kabupaten Nganjuk - Wahid Muhammad Shodiq; M. Zul Mazwan; Sutawi Sutawi; Gunawan Gunawan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Enhanced recognition of the potential of organic fertilizers in promoting sustainable agriculture has stimulated the development of novel fertilizers. However, the more incredible difficulty lies in the parties' level of acceptance towards the ribost fertilizer. This study aims to identify the determinants that impact agricultural stores' acceptance of ribost fertilizer in the Rejoso District, Nganjuk Regency. September through December of 2023, the investigation was conducted in Rejoso District, Nganjuk Regency. Twenty associates willing to supply their stores with ribost fertilizer for sale on the market comprised the total sample. Utilizing WarpPLS, data is analyzed via structural equation modeling-partial least squares (SEM-PLS). Three of the four paths identified by the research findings were found to have a significant impact on agricultural shops' adoption of ribost fertilizer. The level of suitability of ribost fertilizer (X2), the quality of ribost fertilizer service (X3), and emotional factors regarding ribost fertilizer (X4) are identified as the variables that impact agricultural shops' acceptability of ribost fertilizer (Y). Moreover, the path Concurrently, the impact of the independent variable on the acceptance of ribost fertilizer (Y) by agricultural stores reached 74%.